2009
DOI: 10.1089/dna.2008.0850
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Foreign Nucleic Acids in Kidney Tubular Epithelial Cells Deficient in Proapoptotic Endonucleases

Abstract: Degradation of DNA during gene delivery is an obstacle for gene transfer and for gene therapy. DNases play a major role in degrading foreign DNA. However, which of the DNases are involved and whether their inactivation can improve gene delivery have not been studied. We have recently identified deoxyribonuclease I (DNase I) and endonuclease G (EndoG) as the major degradative enzymes in the mouse kidney proximal tubule epithelial (TKPTS) cells. In this study, we used immortalized mouse TKPTS cells and primary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Digital images of the gel were acquired using FluorChem HD2 system (ProteinSimple, Santa Clara, CA) with UV light. The relative amount of endonuclease activity was calculated based on the density of the three bands for plasmid DNA present in covalently closed circular DNA (Type I), open circular DNA (Type I), or linear DNA (Type III) as was previously described 20, 21 .…”
Section: Methodsmentioning
confidence: 99%
“…Digital images of the gel were acquired using FluorChem HD2 system (ProteinSimple, Santa Clara, CA) with UV light. The relative amount of endonuclease activity was calculated based on the density of the three bands for plasmid DNA present in covalently closed circular DNA (Type I), open circular DNA (Type I), or linear DNA (Type III) as was previously described 20, 21 .…”
Section: Methodsmentioning
confidence: 99%
“…However, 99% of the time DNA fragmentation is provided by endogenous cellular enzymes traditionally called "apoptotic endonucleases" (Hengartner, 2001). Studies showed that same enzymes participate in other types of cell death, particularly, necrosis (Singh et al, 2013), and prevent the entering of extracellular DNA into the cell (Buzder et al, 2009). Most studied of these endonucleases are deoxyribonuclease I (DNase I) and endonuclease G (EndoG).…”
Section: Introductionmentioning
confidence: 99%
“…DNase I is mainly expressed in tubular epithelial cells, where it represent 80% of all endonuclease activity [ 33 , 46 ]. However, DNase I is also found in glomeruli [ 31 ].…”
Section: Discussionmentioning
confidence: 99%